Influence of sulfadiazine on anaerobic fermentation of waste activated sludge for volatile fatty acids production: Focusing on microbial responses. (March 2019) - Xie, Jing; Duan, Xu; Feng, Leiyu; Yan, Yuanyuan; Wang, Feng; Dong, Haiqing; Jia, Renyong; Zhou, Qi
Abstract: Extensive studies on anaerobic fermentation of waste activated sludge (WAS) for volatile fatty acids (VFAs) production focused on the effects of operating parameters and pretreatment methods, and little information is available for those of organic pollutants which were absorbed on sludge. The influence of sulfadiazine (SDZ), a typical antibiotic pollutant in WAS, on VFAs production during anaerobic fermentation was investigated in this study. The accumulation of VFAs was remarkably affected in the presence of SDZ. When the content of SDZ was 50 mg per kilogram dry sludge the concentration of VFAs from sludge was 2032.8 mg COD/L, much higher than that of control (1540.2 mg COD/L). Mechanism investigation revealed that the content of extracellular polymeric substances (EPS) from sludge was increased due to the presence of SDZ, which provided more substrates, i.e., protein and carbohydrate, and created a favorable environment for anaerobes. The hydrolysis and acidification of WAS were stimulated by SDZ, and the functional microorganisms were advantageous to VFAs production. The activities of protease, α-glucosidase and acetate kinase were promoted when SDZ occurred, which were beneficial for hydrolysis and acidification. The effect of SDZ on pure strains further confirmed that the formation of VFAs during anaerobic fermentation was stimulated by SDZ. Graphical abstract: Image 1 Highlights: VFAs from sludge during anaerobic fermentation were increased by sulfadiazine. The hydrolysis and acidification of sludge were accelerated by sulfadiazine. Activities of hydrolase and acetate kinase were promoted by sulfadiazine. Sulfadiazine stimulated anaerobes to produce more extracellular polymeric substances. Sulfadiazine contributed to a favorable environment for acid-forming bacteria.